Carbon dioxide and water co-adsorption on the low-index surfaces of TiC, VC, ZrC and NbC: a DFT study. Issue 20 (14th May 2019) - Quesne, Matthew G.; Roldan, Alberto; de Leeuw, Nora H.; Catlow, C. Richard A.
Abstract : We present a theoretical DFT study into the activation of CO2 and H2 O by four low-index surfaces of TiC, VC, ZrC and NbC. Two distinct chemisorption pathways are found for CO2 activation, whilst multiple surface mediated interactions between H2 O and CO2 are reported. Abstract : We present a theoretical DFT study into the activation of CO2 by TiC, VC, ZrC and NbC. Particular focus is given to the study of CO2 /H2 O co-adsorption and interaction on four carbide low-index surfaces: {001}, {011}, carbon-terminated {111} and metal-terminated {111}. The adsorption and activation of CO2 is shown to be most exothermic and indeed barrierless on the metal-terminated {111} surfaces, whilst adsorption on the {001} and {011} planes occurs via a small activation energy barrier. In contrast, the carbon-terminated {111} surface proves to be unstable in the presence of the adsorbates. Both water and carbon dioxide adsorb most strongly on TiC and most weakly on NbC, with the strongest co-adsorption interactions being seen in conformations that maximise hydrogen-bonding.